The Progressive Exegesis of Prophet Ismā’īl’s Sacrifice: Contextual and Symbolic Interpretation - Fawaid, Ahmad; Thahir, A. Halil (QOF, 2025)
The narrative of Prophet Ismāʾīl’s sacrifice holds a central place in the exegetical tradition of the Qur’an, historically interpreted through literal and historical lenses by classical scholars. However, progressive Qur’anic hermeneutics provide a more contextual reading that resonates with the ethical and societal dynamics of contemporary life. This study revisits the story of Prophet Ismāʾīl’s sacrifice using a progressive exegetical approach by exploring the interpretations of three influential scholars: Muḥammad ‘Abduh, Muḥammad Ḥusain Ṭabaṭaba’ī, and Hamka. Employing a qualitative methodology and an extensive literature-based analysis, the study demonstrates that progressive interpretations do not merely critique literalism but emphasize deeper spiritual and ethical dimensions—particularly the concept of total submission (aslama) to God, the reinforcement of spiritual education within the family, and the exemplification of personal sacrifice for the collective good. The narrative is also interpreted as a symbolic model for the parent-child relationship in fostering communication, trust, and social piety. The findings affirm that progressive exegesis offers a constructive bridge between scriptural texts and contemporary contexts, enhancing the applicability and vitality of Qur’anic teachings in addressing modern spiritual, educational, and ethical challenges.